OP0272 Chronic low back pain and anxiety: significant decrease with glucosamine-chondroitin sulfate treatment in a large, community-based, pilot, open prospective interventional study. (15th June 2017) - Singh, G; Alekseeva, L; Goriachev, D; Barinov, A; Nasonov, E; Mithal, A
Abstract : Background: Low back pain (LBP) is associated with 2.3, 2.2, and 1.6 times greater odds for mood disorders, anxiety disorders and alcohol abuse respectively (1). Continued anxiety may lead to a state of "learned helplessness", and both can propagate in a vicious cycle. Glucosamine-chondroitin sulfate (GCS) combination is widely used in the treatment of OA; however there are few prospective studies of its therapeutic merits in LBP. Objectives: To study the efficacy of GCS in the decreasing anxiety in patients with chronic LBP in a large open pilot prospective study. Methods: We enrolled patients 40 - 65 years of age who had LBP for >12 weeks with pain intensity >3 on a 0–10 point VAS in a single-arm, open-label prospective interventional study. Major exclusion criteria were the presence of fibromyalgia, spondylolisthesis, and alcohol and/or drug abuse. All patients were treated with ARTRA (combination glucosamine hydrochloride 500 mg - chondroitin sulfate 500 mg in tablet form; Unipharm Inc.) at a dose of 1 tab bid for the first month and then 1 tab daily for the next two months. The primary endpoint was pain intensity as measured on a 0–10 point VAS. Secondary endpoints included anxiety levels measured by Spielberger's State Trait Anxiety Inventory (STAI) adapted for Russia by Khanin (2). STAI evaluates the current "state" of anxiety, asking how respondents feel "right now, " using items that measure subjective feelings of apprehension, tension, nervousness, worry, and activation/arousal of the autonomic nervous system as well as aspects of "anxiety proneness, " including general states of calmness, confidence, and security ("trait"). Scores for each scale range from 20 to 80, with higher scores indicating greater anxiety. Results: A total of 8, 598 subjects (mean age 52.1 years, 67.3% women, mean BMI 27.4) were enrolled in the study, and formed the intent-to-treat (ITT) population. All but 95 subjects (1.1%) completed the study. Previously-reported ITT analysis with worst observation carried forward showed an improvement in pain at rest from mean (± SD) of 5.2±1.9 at study entry to 1.4±1.6 at 3 months (p<0.0001). Pain at movement decreased from 6.8±1.6 to 2.2±1.8 (p<0.0001). There was a strong correlation between increasing baseline STAI scores and baseline pain at rest and movement (both p<0.0001). After 12 weeks of GCS treatment, STAI "state" anxiety scores dropped from 49.3 (95% CI 49.1 to 49.6) to 35.8 (95% CI 35.6 -36.0) (p<0.0001). A similar reduction was seen in "trait" anxiety scores from 48.3 (95% CI 48.0–48.5) to 39.6 (95% CI 39.3–39.8) (p<0.001). Conclusions: Although open and uncontrolled, this large pilot community-based study shows dramatic reductions in pain and anxiety (both "state" and "trait") in patients with LBP treated with GCS. With its benign safety profile, GCS therapy deserves serious evaluation in the management of LBP in a prospective randomized double-blinded clinical trial. References: Demyttenaere, K., et al., Mental disorders among persons with chronic back or neck pain. Pain, 2007. 129:332–42. Spielberger, C. D. (1989). State–Trait Anxiety Inventory: A comprehensive bibliography. Palo Alto, CA: Consulting Psychologists Press. Disclosure of Interest: G. Singh Grant/research support from: Unipharm Inc., L. Alekseeva: None declared, D. Goriachev Consultant for: Unipharm Inc., A. Barinov: None declared, E. Nasonov: None declared, A. Mithal: None declared